Efek Perbedaan Temperatur terhadap Aktivitas Tripsin-Like dan Amilase Digesti Ikan Lunjar (Rasbora lateristriata Blkr.) - Fadhna Alunka Majid; Untung Susilo; Eko Setio Wibowo; Yulia Sistina (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Previous studies related to digestive enzyme activity have been carried out, but there is no information related to the effect of temperature on the trypsin-like activity and digestive amylase in Rsbora lateristriata. Therefore, the purpose of this study was to determine the effect of temperature differences on the activity of trypsin-like and amylase digestion of Rasbora lateristriata fish. The temperature treatments applied were 20, 30, 40, 50, 60, and 70ºC and each treatment was repeated five times. A total of 125 Rasbora fish with a body weight of 0.81 ± 0.09 grams were used in this study. Trypsin-like and amylase activities were measured using a spectrophotometer. The results showed that there were significant differences (p < 0.05) in the trypsin-like and amylase activities at different temperatures. The trypsin-like activity was not significantly different (p < 0.05) between 20-50ºC, but the activity was lower at 60-70ºC. Amylase activity at 30°C and 40°C was not significantly different (p < 0.05), but significantly different from 20, 50, 60, and 70°C. In conclusion, trypsin-like decreased activity at 60°C and amylase at 50°C.